2007
DOI: 10.5194/acp-7-4445-2007
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous uptake of the C<sub>1</sub> to C<sub>4</sub> organic acids on a swelling clay mineral

Abstract: Abstract. Mineral aerosol is of interest due to its physiochemical impacts on the Earth's atmosphere. However, adsorbed organics could influence the chemical and physical properties of atmospheric mineral particles and alter their impact on the biosphere and climate. In this work, the heterogeneous uptake of a series of small organic acids on the swelling clay, Na-montmorillonite, was studied at 212 K as a function of relative humidity (RH), organic acid pressure and clay mass. A high vacuum chamber equipped w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 50 publications
(105 reference statements)
2
30
0
Order By: Relevance
“…At 298 K, positive bands at 1343, 1424, 1468, 1578, 2935, 2986, and 3016 cm −1 , accompanied by a broad negative band at 3706 cm −1 , indicated the formation of acetate by the consumption of surface OH groups on α‐Al 2 O 3 , based on previous studies . On lowering the reaction temperature, several changes in the spectra were observed.…”
Section: Resultssupporting
confidence: 58%
“…At 298 K, positive bands at 1343, 1424, 1468, 1578, 2935, 2986, and 3016 cm −1 , accompanied by a broad negative band at 3706 cm −1 , indicated the formation of acetate by the consumption of surface OH groups on α‐Al 2 O 3 , based on previous studies . On lowering the reaction temperature, several changes in the spectra were observed.…”
Section: Resultssupporting
confidence: 58%
“…After exposure of CaCO 3 aerosol particles to CH 3 COOH(g), Prince et al 37 found that calcium acetate and CO 2 were formed on the particles and in the gas phase, respectively. The uptake of CH 3 COOH(g) onto Namontmorillonite particles was studied at 212 K, 38 and the uptake coefficients were found to increase from 1.3×10 -5 at 0% relative humidity (RH) to 6.0×10 -5 at 45% RH. Diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) was used to investigate the heterogeneous interaction of CH 3 COOH(g) with α-Al 2 O 3 particles, 39 and the uptake coefficient was reported to be (6.0±0.8)×10 -7 at 0% RH.…”
Section: Introductionmentioning
confidence: 98%
“…Photochemical loss is relatively slow (τ ∼ 25 days), so that any HCOOH formed or vented outside of the boundary layer can be transported for long distances in the free troposphere (Paulot et al, 2011). Irreversible uptake on dust can be significant under some conditions, but appears to be minor on a global scale (Hatch et al, 2007;Paulot et al, 2011). The overall atmospheric lifetime for HCOOH is estimated at 3-4 days (Stavrakou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%